Functional spectrum and specificity of mitochondrial ferredoxins FDX1 and FDX2 - Schulz, Vinzent; Basu, Somsuvro; Freibert, Sven-A; Webert, Holger; Boss, Linda; Mühlenhoff, Ulrich; Pierrel, Fabien; Essen, Lars-O; Warui, Douglas M; Booker, Squire J; Stehling, Oliver; Lill, Roland (Nature chemical biology, 2023)
Ferredoxins comprise a large family of iron-sulfur (Fe-S) proteins that shuttle electrons in diverse biological processes. Human mitochondria contain two isoforms of [2Fe-2S] ferredoxins, FDX1 (aka adrenodoxin) and FDX2, with known functions in cytochrome P450-dependent steroid transformations and Fe-S protein biogenesis. Here, we show that only FDX2, but not FDX1, is involved in Fe-S protein maturation. Vice versa, FDX1 is specific not only for steroidogenesis, but also for heme a and lipoyl cofactor biosyntheses. In the latter pathway, FDX1 provides electrons to kickstart the radical chain reaction catalyzed by lipoyl synthase. We also identified lipoylation as a target of the toxic antitumor copper ionophore elesclomol. Finally, the striking target specificity of each ferredoxin was assigned to small conserved sequence motifs. Swapping these motifs changed the target specificity of these electron donors. Together, our findings identify new biochemical tasks of mitochondrial ferredoxins and provide structural insights into their functional specificity.
Keywords: Ferredoxins; Protein Isoforms; Mitochondria; protein - isoformy; systém (enzymů) cytochromů P-450; proteiny obsahující železo a síru; lidé; Cytochrome P-450 Enzyme System; ferredoxiny; mitochondrie; Humans; Iron-Sulfur Proteins